Short term effects of schumann resonance (7.83hz) on the crowing of mungbean [(vigna radiata (l.) wilzeck)] - Norfahana Zakaria (2014)
This study is intended to show the effects of sound (Schumann Resonance) on the growth of the mungbean at different sound intensities of Schumann Resonance which is slow (60 db), medium (70 db), high (80 db) and control (without any sound). The experiment is design in Completely Randomized Design (CRD) with nine replications. This study is conducted in Universiti Malaysia Kelantan, Jeli. Results on this study revealed that the slow intensity sound is significantly diference with the germination percentage of mungbean. While, the medium sound intensity show highly significant on plant height, leaf numbers, leaf area, fresh weight and dry weight. On the contrary, root length is not significantly difference in all treatments. This study suggested that sound (Schumann Resonance) affect on the growth of the mungbean on certain parameters observed.